2022
DOI: 10.1128/spectrum.02170-21
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation and Functional Characterization of the Plasmid-Borne oqxAB Genes in Salmonella Typhimurium

Abstract: The transferable mechanisms of quinolone resistance (TMQR) gene, oqxAB , has been widely detected in Salmonella and is commonly associated with aac(6′)-Ib-cr . It is thought to be associated with fluoroquinolone resistance, while its ancestor gene from K. pneumoniae is not. This study evaluated the actual role of the plasmid-borne oqxAB genes in Salmonella and showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The plasmid genes qnrA , qnrB , qnrD , and qnrS encode proteins of the pentapeptide repeat sequence family, which protect DNA gyrase and topoisomerase IV from FQ-mediated inhibition ( 11 ). FQ resistance can also result from its acetylation with an appropriate amino nitrogen target mediated by a variant of the common aminoglycoside acetyltransferase gene aac(6′)-Ib-cr ( 12 ). A third mechanism involves the plasmid-based efflux pump-encoding genes qepA ( 13 ) and oqxAB ( 12 , 14 ), which enhance FQ clearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid genes qnrA , qnrB , qnrD , and qnrS encode proteins of the pentapeptide repeat sequence family, which protect DNA gyrase and topoisomerase IV from FQ-mediated inhibition ( 11 ). FQ resistance can also result from its acetylation with an appropriate amino nitrogen target mediated by a variant of the common aminoglycoside acetyltransferase gene aac(6′)-Ib-cr ( 12 ). A third mechanism involves the plasmid-based efflux pump-encoding genes qepA ( 13 ) and oqxAB ( 12 , 14 ), which enhance FQ clearance.…”
Section: Introductionmentioning
confidence: 99%
“…FQ resistance can also result from its acetylation with an appropriate amino nitrogen target mediated by a variant of the common aminoglycoside acetyltransferase gene aac(6′)-Ib-cr ( 12 ). A third mechanism involves the plasmid-based efflux pump-encoding genes qepA ( 13 ) and oqxAB ( 12 , 14 ), which enhance FQ clearance. In addition, it has been reported that the use of enrofloxacin causes an increase in the abundance of antibiotic resistance genes (ARGs) encoding resistance to macrolide-lincosamide-streptogramin, aminoglycosides, and tetracyclines.…”
Section: Introductionmentioning
confidence: 99%